2014
DOI: 10.1007/s00382-014-2430-z
|View full text |Cite
|
Sign up to set email alerts
|

The energy balance over land and oceans: an assessment based on direct observations and CMIP5 climate models

Abstract: surface albedo and emissivity, we infer a surface absorbed solar and net thermal radiation of 136 and −66 Wm −2 over land, and 170 and −53 Wm −2 over oceans, respectively. The surface net radiation is thus estimated at 70 Wm −2 over land and 117 Wm −2 over oceans, which may impose additional constraints on the poorly known sensible/latent heat flux magnitudes, estimated here near 32/38 Wm −2 over land, and 16/100 Wm −2 over oceans. Estimated uncertainties are on the order of 10 and 5 Wm −2 for most surface and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
323
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 280 publications
(354 citation statements)
references
References 70 publications
(133 reference statements)
28
323
2
1
Order By: Relevance
“…Although these low biases have generally decreased over time, increases in observed time series as suggested above may imply that the underestimation of DLR continues to be a serious issue even in the latest generation of climate models used in the IPCC Fifth Assessment Report (Wild et al, 2015). In the context of the quantification of the global energy balance, estimates making use of the information contained in the surface observations (Ohmura and Gilgen, 1993;Wild et al, 1998Wild et al, , 2015 over many years have suggested a higher global mean DLR than typically advocated in various published global energy balance estimates such as those given in the IPCC assessments up to the Fourth Assessment Report. An increase in observed DLR time series may further support such higher DLR estimates within the global energy balance.…”
Section: Bsrn Archives: Application Of Possible New Wsg and Wisg Refementioning
confidence: 99%
“…Although these low biases have generally decreased over time, increases in observed time series as suggested above may imply that the underestimation of DLR continues to be a serious issue even in the latest generation of climate models used in the IPCC Fifth Assessment Report (Wild et al, 2015). In the context of the quantification of the global energy balance, estimates making use of the information contained in the surface observations (Ohmura and Gilgen, 1993;Wild et al, 1998Wild et al, , 2015 over many years have suggested a higher global mean DLR than typically advocated in various published global energy balance estimates such as those given in the IPCC assessments up to the Fourth Assessment Report. An increase in observed DLR time series may further support such higher DLR estimates within the global energy balance.…”
Section: Bsrn Archives: Application Of Possible New Wsg and Wisg Refementioning
confidence: 99%
“…Valdivieso et al [2015] showed that most reanalysis products feature a bias during the period 1993-2009 in the global-mean net surface flux in the order of 1-2 W/m 2 which is larger than the energy gain derived from estimates of the top of atmosphere (TOA) imbalance of about 0.50 (±0.43) W/m 2 [Loeb et al, 2012]. For comparison, the current generation of climate models of the Coupled Model Intercomparison Project Phase 5 (CMIP5) exhibits an uncertainty in the net surface and TOA fluxes in the order of 10 W/m 2 and 5 W/m 2 , respectively [Wild et al, 2015]. However, the extent to which these uncertainties in simulated air-sea fluxes impact the ocean circulation and ocean heat uptake (OHU) in climate models is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The global mean annual volume of evaporation has been intensively debated in recent years (see, e.g., Wang and Dickinson, 2012), with the range of reported global averages in current Coupled Model Intercomparison Project Phase 5 (CMIP5) models being large (Wild et al, 2014) and observational benchmark data sets also differing significantly . In this section, we aim to give some context to the global magnitude of evaporation that results from the WACMOS-ET analyses by contrasting the results with alternative evaporation data sets and existing literature.…”
Section: Global Magnitude Of Terrestrial Evaporationmentioning
confidence: 99%